Interactions between monetary and fiscal policies - Afonso, António (2022)
Using a panel data set of the 28 EU countries from 1970 to 2015, we study the nature of monetary and fiscal policies of both respective authorities and assess how economic and institutional events influence each authority’s reaction functions. Our results show that, for the all period under analysis and controlling for institutional variables, inflation has a significant impact on monetary policy, and that governments raise their primary balances when facing increases in government debt. We also find a substitution relationship between both policies, whereby the central bank assumes an active role, especially in cases of higher levels of debt. Furthermore, the introduction of a common currency shared by 19 out of 28 EU countries had a structural impact on the response and the interaction between the two policies.